Ensuring equine biosecurity at London 2012. (2nd February 2013) - Slater, Josh
Abstract : The London 2012 Olympic and Paralympic Equestrian Games were the highest profile event in the 2012 equestrian calendar and were the culmination of four years of detailed and meticulous biosecurity planning to ensure that all horses arrived, competed and returned home safely and in good health. Josh Slater, Anthony Greenleaves and Andy Paterson describe how this was achieved